Analysis of commercial grape juices - Pezzi, Germano Mansueto; Fenocchio, Paolo (Pesquisa Agropecuaria Brasileira, 2014)
Twelve commercial grape juices, representing the majority of grape juices presentely marketed in Brazil, were analysed. With reference to the "Standards of Identity and Quality of Crape Juices" established by the National Commission for Food Norms and Standards (CNNPA), it was established that: a) two grape juices contained an iron content higher than 15 mg per liter, the maximum content permitted and b) five grape juices contained a sulfur dioxide content higher than 200 mg per liter, the maximum content permitted.